2017
DOI: 10.1093/mnras/stx1254
|View full text |Cite
|
Sign up to set email alerts
|

Accurate orbit propagation in the presence of planetary close encounters

Abstract: We present an efficient strategy for the numerical propagation of small Solar System objects undergoing close encounters with massive bodies. The trajectory is split in several phases, each of them being the solution of a perturbed two-body problem. Formulations regularized with respect to different primaries are employed in two subsequent phases. In particular, we consider the Kustaanheimo-Stiefel regularization and a novel set of non-singular orbital elements pertaining to the Dromo family. In order to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…This suggests that, for this specific case, the use of EDROMO orbital elements, KS regularization and trajectory splitting methods is not necessary to achieve satisfactory results. The computational time of our approach is also significantly better than that reported by Amato et al (2017) on their approach. While it is always unfair to compare CPU times obtained in heterogeneous setups, we note how this observation is compatible with what reported in Figure 3, considering that in this case the number of planets is 𝑁 = 3 and the numerical techniques we compare to are both very similar to IAS15…”
Section: (99942) Apophis Close Earth Encountermentioning
confidence: 63%
See 2 more Smart Citations
“…This suggests that, for this specific case, the use of EDROMO orbital elements, KS regularization and trajectory splitting methods is not necessary to achieve satisfactory results. The computational time of our approach is also significantly better than that reported by Amato et al (2017) on their approach. While it is always unfair to compare CPU times obtained in heterogeneous setups, we note how this observation is compatible with what reported in Figure 3, considering that in this case the number of planets is 𝑁 = 3 and the numerical techniques we compare to are both very similar to IAS15…”
Section: (99942) Apophis Close Earth Encountermentioning
confidence: 63%
“…Interestingly, two different numerical integration schemes are considered, XRA15 and LSODAR, both based on the Everhart-Radau numerical scheme (Everhart 1985) improved with the adaptive step size strategy proposed by Rein & Spiegel (2015), and thus resulting in numerical schemes similar to IAS15 4 . In Table 2 we summarize the comparison between our Taylor scheme and the results reported in Amato et al (2017). Interestingly, our approach is able to reach better or equivalent precision even if based on the straight forward Cowell's method.…”
Section: (99942) Apophis Close Earth Encountermentioning
confidence: 89%
See 1 more Smart Citation
“…Symplectic integration methods, which are based on the rigorous conservation of an approximate Hamiltonian of the problem, are commonly used in astrophysical research to perform extremely long integrations and may seem like a feasible candidate for the study. Nevertheless, we do not take them into account in this work since previous research has shown that the conservation of the symplectic structure does not necessarily imply the reduction of errors in position and velocity (Amato et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The special perturbation method generated from the new elements can exhibit a substantial advantage with respect to Dromo. Numerical investigations conducted by Amato et al (2017Amato et al ( , 2019 show its excellent behaviour in the propagation of both asteroids and artificial satellites of the Earth. An analogous formulation was derived independently by Roa and Peláez (2015) and Baù et al (2016) for positive values of the Keplerian and total energy, respectively.…”
mentioning
confidence: 99%